(untitled) (OODBODHAN, 2024)
The Parabolic Dish Solar Concentrator (PDSC) plays a vital role in harnessing solar energy efficiently. Harnessing solar energy effectively is crucial in the quest for sustainable energy solutions, and the Parabolic Dish Solar Concentrator stands out as a promising and simple technology in this regard. The parabolic dish solar concentrator, with a 1.84-meter aperture diameter, 0.342-meter depth, and 0.619-meter focal length, was designed, fabricated, and tested. Using a concentrating reflector, heat from the sun is focused on a receiver. The main objective of the project is to design, fabricate, and test the Parabolic Dish Solar Concentrator. At the focal point, the collected energy is used for heating water and cooking rice, eggs, and potatoes in the receiver. The receiver arrangement is supported by a four-bar mechanism, ensuring that the sun’s rays are always directed toward the receiver at different times of the day. On a sunny, cloud-free day, the maximum temperature recorded was 370°C. The water heating thermal efficiency obtained was 24.67%. The cooking time varies due to the intensity of solar radiation and the time of day. It was observed that during mid-day, the cooking time was shorter because of the higher intensity of solar radiation.